Transformation Equations for the Fifth Dimension - M. Helmy Said (New Frontiers in Physical Science Research Vol. 8, 2023)
Scientists have been arguing for a long time if there are particles faster than the speed of light or not. Those who denied the existence of particles faster than light speed always refer to Lorentz equation. This equation deals with particles in only four dimensions. In this paper, we show what would happen if we add one more dimension to this equation to make it deals with five dimensions instead of four. The addition of this fifth dimension will greatly help us understand the state of particles before, near, at, and above the speed of light.